Enhancement of Drilling Fluid Properties Using Nanoparticles - Al-Mahdawi, Faleh H. M.; Saad, Karrar (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Nanotechnology has shown a lot of promise in the oil and gas sectors, including nanoparticle-based drilling fluids. This paper aims to explore and assess the influence of various nanoparticles on the performance of drilling fluids to make the drilling operation smooth, cost effective and efficient. In order to achieve this aim, we exam the effect of Multi Wall Carbon Nanotube and Silicon Oxide Nanoparticles as Nanomaterial to prepare drilling fluids samples. Anew method for mixing of drilling fluids samples using Ultra sonic path principle will be explained. Our result was drilling fluids with nano materials have high degree of stability. The results of using Multiwall Carbon Nanotube and Silicon Oxide show that MWCNT have an effect on rheological properties more than SiO2 and good thermal conductivity. Also, both nano particles have potential effect on filter loss and stability of mud. The change in density was insignificant which is beneficial for many drilling operations.